A Wearable Colorimetric Dosimeter to Monitor Sunlight Exposure. Issue 6 (23rd April 2018) - Wang, Junxin; Jeevarathinam, Ananthakrishnan Soundaram; Jhunjhunwala, Anamik; Ren, Haowen; Lemaster, Jeanne; Luo, Yanqi; Fenning, David P.; Fullerton, Eric E.; Jokerst, Jesse V.
Abstract: The personal ultraviolet (UV) dosimeter is a useful measurement tool to prevent UV induced dermal damages; however, conventional digital dosimeters are either bulky or require external power sources. Here, a wearable, colorimetric UV film dosimeter that provides color transition, from purple to transparent, is reported to indicate the UV dose. The film dosimeter is made of a purple photodegradable dye ((2Z, 6Z)‐2, 6‐bis(2‐(2, 6‐diphenyl‐4H‐thiopyran‐4‐ylidene)ethylidene)cyclohexanone or DTEC) blended in low density polyethylene film. The DTEC film discolored 3.3 times more under the exposure of UV light (302 nm) than visible light (543 nm), and a UV bandpass filter is developed to increase this selectivity to UV light. The DTEC film completely discolors to transparency in 2 h under an AM 1.5 solar simulator, suggesting the potential as an indicator for individuals with types I–VI skin to predict interventions to avoid sunburn. Finally, the DTEC film is integrated with the UV bandpass filter on a wristband to function as a wearable dosimeter for low cost and convenient monitoring of sunlight exposure. Abstract : This colorimetric dosimeter indicates ultraviolet (UV) dose with a color transition from purple to transparent for intervention predictions. The initial purple color of the dosimeter can be customized to suit individual preference of sunlight exposure time. This power‐free, waterproof dosimeter is equipped with a UV bandpass filter to enhance UV selectivity and fashioned with a wristband for wearable applications.